A Qualitative Case Study on the Adoption of Smart Warehouse Approaches in Malaysia - Reima Kutty Krishnan Elizabeth; Norida Wahab Siti (E3S Web of Conferences, 2019)
This qualitative case study explores the factors that influence the adoption of smart warehouse in Malaysia. Purposive sampling is used to carry out this research by conducting interview discussion with several respondents. Lack of warehouses in Malaysia is that adopt smart warehouse and still on manual operation. In this study, a discussion report would be done relating to the TOE framework (technological, organizational and environmental) influences in adopting smart warehousing. The types of technologies being implemented in the warehouses in Malaysia are being evaluated and further discussed on the similarity of thoughts. The findings of this research show that most respondents agree that implementing smart warehouse approaches would bring relative advantage. Warehouses in Malaysia in terms of technology implementation are still at very surface and backwards. Top management and cost are two factors that would influence organization readiness towards smart warehousing, whereas external pressure, government support and geographical location would influence the adoption of smart warehousing. This research can be used as a reference for future researches on encouraging warehouses in Malaysia to adopt smart warehouse approaches.